2014
DOI: 10.1371/journal.pone.0085926
|View full text |Cite|
|
Sign up to set email alerts
|

CXCR7 Is Highly Expressed in Acute Lymphoblastic Leukemia and Potentiates CXCR4 Response to CXCL12

Abstract: Recently, a novel CXCL12-binding receptor, has been identified. This CXCL12-binding receptor commonly known as CXCR7 (CXC chemokine receptor 7), has lately, based on a novel nomenclature, has received the name ACKR3 (atypical chemokine receptor 3). In this study, we aimed to investigate the expression of CXCR7 in leukemic cells, as well as its participation in CXCL12 response. Interesting, we clearly demonstrated that CXCR7 is highly expressed in acute lymphoid leukemic cells compared with myeloid or normal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 52 publications
4
46
0
Order By: Relevance
“…The additional inhibition of the CXCR7 receptor demonstrated a supplemental and so far unknown anti-inflammatory effect on PMN migration. A possible explanation for this finding could be that CXCR7 is known to potentiate the effect of CXCR4 (17), which also seems to be the case in terms of antagonism. The mechanism behind this might be the impact of CXCR7 on gene and protein expression of SDF-1 and CXCR4.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The additional inhibition of the CXCR7 receptor demonstrated a supplemental and so far unknown anti-inflammatory effect on PMN migration. A possible explanation for this finding could be that CXCR7 is known to potentiate the effect of CXCR4 (17), which also seems to be the case in terms of antagonism. The mechanism behind this might be the impact of CXCR7 on gene and protein expression of SDF-1 and CXCR4.…”
Section: Discussionmentioning
confidence: 92%
“…To the best of our knowledge, we are the first who determined the expression of CXCR7 on PMNs in acute pulmonary inflammation. Melo et al (17) determined the expression of CXCR7 in human bone marrow and found a detrimental increase of the receptor in terms of acute lymphoblastic leukemia. In their study, protein level of the receptor on PMNs started to decrease 6 h after the inflammation and was significantly reduced after 12 h. This is in line with our finding from the gene expression of CXCR7 in total lungs of mice, where hyperinflammation caused a short-term upregulation of the CXCR7 receptor, which was 24 h after the stimulus had already been downregulated again.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cervical cancer research [30], colorectal cancer research by Xu et al [19] cutaneous squamous cell carcinoma research by Hu et al [21] renal cancer research by Wang et al [26] and gallbladder cancer research by Yao et al [27] all of these studies have consistent results for tumor grade, stage and lymph node metastasis [30][31][32][33][34]. These significant clinicopathological relative factors revealed their roles in tumor development [35][36][37][38][39][40]. This meta-analysis has drawn the distance between CXCR7 and the clinicopathological indicators closer.…”
Section: Discussionmentioning
confidence: 98%
“…Other chemokine receptors that have been detected by flow cytometry in B-ALL include CCR3 and CCR4 [2, 12] as well as CXCR7 (also known as ACKR3), which is strongly upregulated in the bone marrow in B-ALL compared to normal tissue and plays a role in controlling CXCR4-mediated migration [13]. CCR7 cell surface expression has been found to vary between studies [2, 3, 12] while CCR1, CCR2, CCR5 and CCR6 were extremely rarely or never expressed [2, 3, 10, 14].…”
Section: B-cell Acute Lymphoblastic Leukemiamentioning
confidence: 99%